Studi Karakter Umbi dan Kandungan Nutrisi Dioscorea spp. - Eko Sulistyono; Jaminton Marpaung (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
Dioscorea was a member of Dioscoreaceae, ordo of liliales and class of Monocotyledoneae, Two types of Dioscorea were annual and perennial. As much as 50-60 species of 600 species was cultivated as food source. This research was conducted to study tuber characters and nutrition content of Dioscorea sp. Plant material was Dioscorea collection from some places in Indonesia. Five accessions of Dioscorea alata. Dioscorea esculenta and Dioscorea hispida. were analyzed for the content of fat, protein and starch. Tube characters observed were tuber number, tuber weight, length and diameter. There were significant differences of tube character, protein and starch content between Dioscorea accession. The highest tuber weight and starch content were resulted by D.alata especially accession number 49. The highest protein content was resulted by accession number 67 of D. esculenta. Positive correlation between tuber diameter and tuber weight of D. alata showed that higher accumulation of fotosynthate was followed by increasing tuber diameter. In other words, sink capacity was determined by tuber diameter. Key words: Tuber, Dioscorea spp., Nutrition content